Genetics aspects of reproductive performance for Holstein: Al-Samarai F.R .Al-Anbari N.N . and Al-tmimi Y.K. - Al-Samarai, F. R. (The Iraqi Journal of Veterinary Medicine, 2006)
A total of 16678 records of age at first calving and ages at next calving ,in addition to 14058 records of calving interval belonged to Holstein cows wereanalysed over period from 1992 to 2003 , at the Nasr Dairy Cattle Station,United Company for Animal Resources Ltd., Al-Soueira ( 50 Km South ofBaghdad ). Data was analaysed using General Linear Model within the SASprogram to study the effects of some fixed factors on the studied traits .Components of variance for the random effects was estimated by theMinimum Variance Quadratic Unbised Estimation Procedure ( MIVQUE ) , alsophenotypic trend was estimated for all traits .The overall means for age at first calving till the age at sixth calving were48.17 , 62.77 , 77.41 , 91.35 , 105.53 months respectively , and the heritabilityfor the same traits was 0.10 , 0.01 , 0.03 , 0.04 , 0.02 , 0.11 respectively .whereas the overall mean of calving interval and heritability was 458.59 daysand 0.07 .The results obtained that there was a significant effect of year of birth onage at first calving , whereas the season of birth was not .All the estimates of heritability were low so it’s reflect the role ofenvironment factors in the traits variation.Phenotypic trend was negative andsignificant ( p <0.01 ) for age at first calving ( - 1.05 month / year ) and calvinginterval (- 2.03 day / year ) .